MANAGEMENT OF NONFORMAL EDUCATION INSTITUTION IN OPTIMIZING SERVICES TO COMMUNITY: A CASE STUDY - Shofi Nailatul Muyassaroh; Agus Zaenul Fitri (JURNAL AL-TANZIM, 2021)
This study aims to explain the management of optimizing services to the community at nonformal education institutions and provide a role model for managers of community learning centers. This research was conducted at Tunas Pratama Community Learning Center in Blitar with a descriptive qualitative method using a phenomenological approach. Data were collected through in-depth interviews, participant observation, and documentation. The results showed that the management of optimizing services to the community at nonformal education institution at Tunas Pratama Community Learning Center includes four strategies; 1) systematic planning with various activities that promote courage in making decisions; 2) organizing by division of labor based on the responsibilities of each section wrapped in a family culture and organizational climate; 3) implementation of programs with various initiatives that are adaptive to policies, technological advances, integrated psychology, and mental health education and establish many relationships; 4) program supervision is carried out massively, both directly and indirectly, which requires the direct involvement of a leader.